Impact of chisel plowing on soil physical properties in rice (Oryza Sativa L.) cultivation - Castillo-Coronado, Jordan Alexis; Polanía-Montiel , Diana Carolina; Ardila-Marin , Juan Gonzalo (Revista de Ciencias Agrícolas, 2025)
The continuous use of agricultural machinery in rice (Oryza Sativa L.) cultivation throughout its vegetative cycle increase in apparent density and resistance to penetration into the soil, which affects the development of the crop and its performance. Thus, seeking a more sustainable agriculture, it was proposed to evaluate the soil’s physical properties and crop yield, modifying the conventional preparation with a harrow using a chisel on the USCO’s Farm in Palermo (Huila, Colombia). Four experimental treatments were implemented: three with different chisel passes and a control with conventional plowing, in which real density, bulk density, and porosity were evaluated before and after tillage, and after harvest. The statistical analysis was carried out through analysis of variance, and the techno-economic analysis was carried out based on the production and operation costs between the two types of tillage. The results showed that after tillage, the bulk density decreased by 13.5% in the control and 11.5% in T3. These effects increased porosity between 23.0 and 31.6% in the area with greater tillage. After the harvest, a resilient response of the soil was found, which recovered 9.5 and 12.4% of the apparent density in T3 and T4, respectively. The use of reduced tillage with chisel did not make a significant difference in production (Control: 7.8 t ha-1, T1 and T2: 8.2 t ha-1, and T3: 8.4 t ha-1), but it was more economical and less aggressive for the soil in structural terms.